Turismo rural y medio ambiente - Villanueva, José (Geographicalia, 2017)
There are numerous interconections between man and the environment, and the kind of tourism which attempst to make the relations between the two as "ecological" as possible is ecotourism. Turism in contact with nature prevails. It contributes to the achievement and maintenance of viable development at the same time as it helps to generate the rural space by conserving its individual personality. A decade has already passed since this formula or rural tourism began to be spread around, with financial support from various administrations. The Alto Sobrarbe Oriental (High Eastern Sobrarbe), in the heart of the Aragonese Pyrenees, with abundant natural and cultural resources, is an area in which the idea of rural tourist accommodation has penetrated and the positive results are already becoming visible. The cultural heritage is refurbished, the urban nuclei revert to a state of certain activity and not only has the descent in the population censuses come to a halt but a slight increase is recorded. In summary, rural tourism is a key to achievirig harmony between the rural and urban population, and between both populations and the natural surroundings.